Invariom based electron density studies on the C/Si analogues haloperidol/sila-haloperidol and venlafaxine/sila-venlafaxine - Luger, Peter; Dittrich, Birger; Tacke, Reinhold (Organic & biomolecular chemistry, 2015)
The subjects of this study are the structures and electron densities of the carbon/silicon analogues haloperidol/sila-haloperidol ( 1a / 1b ) and venlafaxine/sila-venlafaxine ( 2a / 2b ). The parent carbon compounds 1a (an antipsychotic agent) and 2a (an antidepressant) are both in clinical use. For haloperidol/sila-haloperidol, three published structures were studied in more detail: the structures of haloperidol hydrochloride ( 1a ·HCl), haloperidol hydropicrate ( 1a ·HPic) and sila-haloperidol hydrochloride ( 1b ·HCl). For venlafaxine/sila-venlafaxine, the published structures of venlafaxine ( 2a ), venlafaxine hydrochloride ( 2a ·HCl; as orthorhombic ( 2a ·HCl-ortho) and monoclinic polymorph ( 2a ·HCl-mono)) and sila-venlafaxine hydrochloride ( 2b ·HCl) were investigated. Based on these structures, the molecular electron densities were reconstructed by using the invariom formalism. They were further analysed in terms of Bader's quantum theory of atoms in molecules, electrostatic potentials mapped onto electron density isosurfaces and Hirshfeld surfaces. These studies were performed with a special emphasis on the comparison of the corresponding carbon/silicon analogues.